1995
DOI: 10.1007/bf03172926
|View full text |Cite
|
Sign up to set email alerts
|

Activating instruction: How to foster study and thinking skills in higher education

Abstract: New instructional procedures have been developed and applied at the University ofHelsinki. Department ofPsychology since 1986. The aim ofthese procedures has been to enhance effective study skills. The idea is to stimulate active learning in students by so called activating instruction. whi ch is theoretically based on a combination of Vygotsky's ideas. applied cognitive science, and process-oriented instruction.in many courses, students have been able to choose a preferred form of instruction among the new an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 10 publications
2
72
0
3
Order By: Relevance
“…Students are continually activated to carry out the various learning functions when learning (Entwistle, 1992;Lonka & Ahola, 1995). Examples of this teaching strategy for every learning function are presented in Table 3.…”
Section: Teacher-regulation Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Students are continually activated to carry out the various learning functions when learning (Entwistle, 1992;Lonka & Ahola, 1995). Examples of this teaching strategy for every learning function are presented in Table 3.…”
Section: Teacher-regulation Strategiesmentioning
confidence: 99%
“…If the teacher uses a shared regulation form of instruction, congruence between learning and teaching occurs when the students master a learning activity to an intermediate degree. An example of this is that students do not process the subject matter critically on their own initiative, but are nevertheless stimulated by a group discussion to draw their own conclusions and to form personal judgments (Lonka & Ahola, 1995). In this shared-control strategy, constructive friction will take place if students do not master a learning or thinking activity in the subject domain at hand.…”
Section: The Interplay Between Teacher-regulation and Student-regulatmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this educational experiment only covered the first year of an undergraduate program, students who participated graduated at a significantly higher rate than their peers in a control group, and reflected retrospectively that the program had had a strong positive effect on their college careers. Lonka and Ahola (1995) demonstrated that students participating in activating instruction were more successful than those participating in lecture-based courses (although they needed more time in the first years of study).…”
Section: Introductionmentioning
confidence: 99%
“…A writing course for doctoral students is described where different techniques are applied. The exercises are based on those introduced by Björk (1997), Boice (1990), Healy (1986, as well as Lonka and Ahola (1995). …”
mentioning
confidence: 99%